Organoleptic And Nutritional Quality Of Wani Fruit (Mangifera Caesia) Sorbet - Trisdayanti, Ni Putu Eka (Universitas Pendidikan Indonesia, 2021)
Sorbet is one kind of the desserts. Based on the many new variants of sorbet, an idea emerged to make a sorbet with a new variant that has ingredients and benefits that are good for health. In this study focuses on sorbets will be made with the basic ingredients of wani fruit (Mangifera caesia) as its basic ingredient, considering that there has been no research that has processed sorbets with wani fruit (Mangifera caesia) as the base ingredient (Mangifera caesia). In addition, the use of wani fruit (Mangifera caesia) is still limited for fresh consumption, whereas wani fruit (Mangifera caesia) has the potential to be used as a processed product. The author processed the wani fruit (Mangifera caesia) into sorbet, then tested the quality (organoleptic and nutritional). Experiments and organoleptic tests of wani fruit sorbet (Mangifera caesia) were carried out at the Politeknik Pariwisata Bali Bali Tourism Polytechnic campus, and for nutrition tests were carried out at Prodia Food Health Laboratory. The organoleptic results of wani fruit sorbet (Mangifera caesia) are good in terms of taste, aroma, texture, and color, and for the its nutritional content, of wani fruit sorbet (Mangifera caesia) namely consist of 33.1%, of carbohydrates 33.1%, 0.475% of Crude Protein 0.475%, 0.330% of total ash / ash 0.330%, 0.5% of total fat / fat 0.5%, and 65.6% ofÂ water content